Intramembrane proteolysis controls diverse signalling pathways throughout evolution. - Urban, S; Freeman, M (2002)
Regulated intramembrane proteolysis (RIP) has recently emerged as a conserved mechanism for controlling many signalling pathways in both prokaryotes and eukaryotes. Although early examples were confined to the activation of membrane-tethered transcription factors in the cell receiving the signal, recent analysis indicates that RIP also regulates the emission of factors involved in intercellular communication.